Changes in carbon and nitrogen cycling in a floodplain lake over recent decades linked to littoral expansion, declining riverine influx, and eutrophication - Chen, Xu; McGowan, Suzanne; Zeng, Linghan; Xu, Lei; Yang, Xiangdong (Wiley, 2017)
This study aimed to understand changes in the biogeochemical processing of organic matter (OM) in response to multiple stressors (e.g., littoral area expansion, wastewater input, and hydrological regulation) in East Dongting Lake (Central China) over the past 60 years, using analyses of total organic carbon (TOC), total nitrogen (TN), C/N ratios, δ13C, δ15N, and diatoms from 2 sediment cores collected from the littoral and central parts of the lake. OM mainly originated from phytoplankton and C3 plant‐derived soil OM based on the ranges of C/N ratios (from 7 to 11) and δ13C (between −27‰ and −23‰). Littoral area expansion due to siltation caused an increasing influx of terrestrial soil OM in the 1980s and the 1990s, subsequently lowering δ13C values and rising C/N ratios in both sediment cores. Meanwhile, higher δ15N was linked to a high influx of isotopically heavy nitrate from urban and agricultural wastewaters. After 2000, slight decreases in TOC and TN in the littoral area were attributable to reducing inputs of external OM, likely linked to declining sediment influx from the upper reaches resulting from the Three Gorges Dam impoundment. Contrasting increases in TOC, TN, and C/N ratios in the central part indicated a high influx of terrestrial soil OM due to the declining distance from the shoreline with littoral area expansion. Declining δ15N values after 2000 indicated an increase in N2‐fixing cyanobacteria with eutrophication. Changes in diatom assemblages in both the littoral and central zones reflected nutrient enrichment and hydrological alterations. These results indicate that littoral expansion, declining riverine influx, and anthropogenic nutrient inputs are potential driving forces for the biogeochemical processing of OM in floodplain lakes. This study provides sedimentary biogeochemical clues for tracking past limnological conditions of floodplain lakes that are subjected to increasing disturbances from hydrological regulation and eutrophication.